Hemoglobin and bone metastasis risk in breast cancer: a prognostic perspective - Bernardes, Letícia de Barros Souto Barcelona; Guimarães, Ana Jullia Alves; Elias, Hélen Caroline de Carvalho; Salles, Thainá do Espírito Santo; Franca, Giulia Nogueira; Cardoso, Ana Claudia Marinho; Martins Junior, Reynaldo Real; Franca, Carlos Antônio da Silva (Mastology, 2026)
Introduction: Bone is the most common site of breast cancer metastasis, but prognostic factors remain controversial. Objective: This study examined the association between hemoglobin (Hb) levels and bone metastasis (BM) risk. Methods: This retrospective study evaluated 260 breast cancer patients, between 2021–2023, analyzing age, clinical stage (IIIa, IIIb, IIIc), estrogen receptor (ER), progesterone receptor (PR), human epidermal growth factor receptor-type 2 (HER2) status, and Hb levels. Groups were divided into those with and without BM. Treatments included surgery, chemotherapy, radiotherapy, and hormonal blockade for ER/PR-positive cases. HER2 3+ patients received trastuzumab. Statistical analyses included t-tests and chi-square tests. The study was approved by the research ethics committee. Results: The mean age was 61.3 years, standard deviation ±9.7, and mean Hb was 12.3±1.17 g/dL. ER was positive in 71.5% of patients, PR in 59.6%, and HER2 in 25.8%. Clinical stages IIIa, IIIb, and IIIc were observed in 50.8%, 33.5%, and 15.7%, respectively. BM was identified in 17.3% of cases. Among stage IIIa, IIIb, and IIIc, BM occurred in 22.7%, 10.3%, and 14.6%, respectively (p>0.067). BM was found in 16.1% of ER-positive vs. 20.3% of ER-negative patients (p>0.468). PR and HER2 status showed no significant relationship with BM (p>0.508; p>0.708). However, Hb levels were significantly lower in BM patients (11.7 g/dL) than in those without (12.5 g/dL; p<0.0001). Conclusion: Lower Hb levels may be linked to higher BM risk in breast cancer patients and could serve as a prognostic marker, requiring further investigation.